Psychosocial interventions for self-harm in adults - Hawton, Keith; Witt, Katrina G; Taylor Salisbury, Tatiana L; Arensman, Ella; Gunnell, David; Hazell, Philip; Townsend, Ellen; van Heeringen, Kees (Wiley, 2016)
Background: Self-harm (SH; intentional self-poisoning or self-injury) is common, often repeated, and associated with suicide. This is an update of a broader Cochrane review first published in 1998, previously updated in 1999, and now split into three separate reviews. This review focuses on psychosocial interventions in adults who engage in self-harm.